Highly Active and Thermally Stable Supported Pd@SiO2 Core–Shell Catalyst for Catalytic Methane Combustion. Issue 8 (1st April 2016) - Pi, Dong; Li, Wen Zhi; Lin, Qi Zhao; Huang, Qi Fu; Hu, Hui Qing; Shao, Chun Yu
Abstract: A series of Pd‐based core–shell catalysts (Pd@SiO2, Pd@CeO2, and Pd@ZrO2 ) supported on Si‐modified Al2 O3 were prepared for the catalytic combustion of lean methane. Pd@SiO2 exhibited slightly lower catalytic activity than Pd@CeO2 and higher catalytic activity than Pd@ZrO2 in dry conditions; however, Pd@SiO2 had the highest catalytic activity among the three catalysts in the presence of high concentrations of water vapor. Furthermore, the Pd@SiO2 catalyst showed good thermal stability and resistivity to water poisoning. CO chemisorption and TEM results demonstrated that the core–shell structure could help in the stabilization of the active phase compared to the uncoated Pd/Si‐Al2 O3 catalyst. XRD and X‐ray photoelectron spectroscopy results indicated that a balanced mixed phase of PdO x /Pd 0 is the main active phase of these Pd‐based catalysts. Abstract : Don't run into the air, methane : A series of Pd‐based core–shell catalysts (Pd@SiO2, Pd@CeO2, and Pd@ZrO2 ) supported on Si‐modified alumina are prepared for catalytic combustion of lean methane. As the metal particles are coated with different oxide shells, the catalytic activity towards methane oxidation is changed to varying degrees. The experimental results suggest that a balanced mixed phase of PdO x /Pd 0 is the main active phase of these Pd‐based catalysts.